A Case of Bilateral Corneal Perforation in a Patient with Severe Dry Eye - JYOTI DESWAL; SUDESH KUMAR ARYA; AMIT RAJ; ANUBHA BHATTI (Journal of Clinical and Diagnostic Research, 2017)
Dry eye is a common problem affecting mainly the adult population. In severe cases, it can result in sterile corneal ulcer and perforation. We report a rare case of a 26-year-old male, a known patient of severe dry eye who presented with sterile corneal ulcer with corneal perforation in both the eyes. The patient was managed by applying cyanoacrylate glue and bandage contact lens in both eyes and topical antibiotic, topical cyclosporine and preservative free artificial tears at two hourly intervals. The patient was investigated for the systemic cause of severe dry eye but no cause could be ascertained. On follow up, the patient reported marked relief in photophobia. On examination, both eyes showed sealed perforation with well formed anterior chamber. In conclusion, one should examine a dry eye patient carefully and detect corneal ulcers and perforations in time so as to prevent its sequelae.